Big companies ? bigger profits for small farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
IITA assists farmers in Nigeria to market their products to private companies by providing market information and organising bulk selling.